For the first one x=-2
For the second one x= -1/3
six million, thirty thousand <span>6, 030, 000 expressed in scientific notation
</span>
<span>6.03×10^6.</span>
Answer:
y=2x-1
Step-by-step explanation:
y= 6x-1-4x
y=2x-1
(x + 12) = (x + 14) - 3
subtract 12 from each side
x = x + 14 - 3 - 12
Now if we subtract x from each side we see that x - x = 0. Combine the terms left over and we have -1, so
0 = -1
The answer is NO SOLUTION
<span>2(4/2)^2 - 15 + 6
= </span><span>2(2)^2 - 15 + 6
= </span><span>2(4) - 15 + 6
= 8 - 15 + 6
= -1</span>